"Vicinitas": Neighbourhoods, Networks and Identities in Ciceronian Italy - Lomas, Kathryn (Gerión. Revista de Historia Antigua, 2019)
Roman Italy was a highly interconnected region. The social elites of both Rome and other communities were linked by a dense web of connections which played an important role in influencing social, economic and political behaviour and shaping cultural identities. This paper explores the importance of neighbourhood networks in the period after the social war, using the works of Cicero and his contemporaries, as well as modern analytical approaches. It examines how vicinitas is defined and what social and political significance it had in this pivotal period of Roman history.